The seed thief - L'Ange, Jacqui (2015)
" Sometimes the thing you find is not the one you were looking for. When botanist Maddy Bellani is asked to travel to Brazil to collect rare seeds from a plant that could cure cancer, she reluctantly agrees. Securing the seeds would be a coup for the seed bank in Cape Town where she works, but Brazil is the country of her birth and home to her estranged father.Her mission is challenging, despite the help of alluring local plant expert Zé. The plant specimen is elusive, its seeds guarded by a sect wary of outsiders. Maddy must also find her way in a world influenced by unscrupulous pharmaceutical companies and the selfish motives of others.Entrancing and richly imagined, The Seed Thief is a modern love story with an ancient history, a tale that moves from flora of Table Mountain to the heart of Afro-Brazilian spiritualism." -- Publisher's description: http://www.randomstruik.co.za/books/the-seed-thief-/5858
Keywords: Botanists -- South Africa -- Fiction; Rare plants -- Fiction; Man-woman relationships -- Fiction